Pre-Pandemic State of Grocery Purchases Online: An Initiatory Review - Menon, Mohan (Journal of Marketing Development and Competitiveness, 2021)
While the pandemic in 2020 changed shopping as we knew it, changes were already underway in the years earlier. Consumer experience with online shopping has led to more products being bought online and delivered to the home. But this phenomenon does not seem to have carried over to online grocery shopping, a laggard in the ecommerce space. There are several reasons for this oddity. Unlike the typical products bought online such as electronics or clothing, groceries shopping seems to take on additional dimensions. The need to adapt and innovate in this space seem critical. The paper explores this anomaly in this space and tries to offer plausible explanations. Finally, future directions in the marketplace are discussed.